2017
DOI: 10.3390/ijms18020453
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Approaches for Fetal DNA Fraction Estimation in Noninvasive Prenatal Testing

Abstract: The discovery of cell-free fetal DNA molecules in plasma of pregnant women has created a paradigm shift in noninvasive prenatal testing (NIPT). Circulating cell-free DNA in maternal plasma has been increasingly recognized as an important proxy to detect fetal abnormalities in a noninvasive manner. A variety of approaches for NIPT using next-generation sequencing have been developed, which have been rapidly transforming clinical practices nowadays. In such approaches, the fetal DNA fraction is a pivotal paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 50 publications
0
57
0
1
Order By: Relevance
“…Indeed, some laboratories may not be checking FF or using optimal methods for detection that could potentially provide false-negative results to patients [1]. Technical factors that can influence FF and its estimation are sample handling [2] and the choice of bioinformatics tools (reviewed in [3]) [4]. Multiple biological factors have been identified that affect FF, including gestational age [4][5][6][7][8][9], weight and/or body mass index (BMI) [6][7][8][9][10][11][12], trisomies [7,[10][11][12][13], fetal crown-rump length [6,10,12], serum pregnancy-associated plasma protein-A [6,10,12], serum free β-human chorionic gonadotropin [6,10,12], hypertension [7], twins [7], smoking [10], and assisted conception [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some laboratories may not be checking FF or using optimal methods for detection that could potentially provide false-negative results to patients [1]. Technical factors that can influence FF and its estimation are sample handling [2] and the choice of bioinformatics tools (reviewed in [3]) [4]. Multiple biological factors have been identified that affect FF, including gestational age [4][5][6][7][8][9], weight and/or body mass index (BMI) [6][7][8][9][10][11][12], trisomies [7,[10][11][12][13], fetal crown-rump length [6,10,12], serum pregnancy-associated plasma protein-A [6,10,12], serum free β-human chorionic gonadotropin [6,10,12], hypertension [7], twins [7], smoking [10], and assisted conception [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the apparent fetal DNA fractions serve as key parameter in the FEMER algorithm. Even though there are many alternative methods for estimating fetal DNA fraction, SNP‐based methods are still widely considered as the gold‐standard and universal approach for this task . In our algorithm, we used DNA‐seq data but not the BS‐seq data for mining the fetal‐specific informative SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are many alternative methods for estimating fetal DNA fraction, SNP-based methods are still widely considered as the gold-standard and universal approach for this task. 23 In our algorithm, we used DNA-seq data but not the BS-seq data for mining the fetal-specific informative SNPs. We had made this choice because of the following considerations: (i) compared to the DNA-seq data, the BS-seq data showed higher base-calling errors and bias in genome coverage because of the extreme GC content caused by the bisulfite conversion 32 and (ii) more importantly, the informative SNPs deduced from the DNA-seq data would not bias the estimation of the fetal DNA fraction in the BS-seq data as these 2 datasets were generated by independent libraries.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SCM-PGT requires strategies to discriminate between exogenous and maternal DNA and embryonic DNA in SCM to improve the general and full concordance rates, but this was only carried out in 30% (three out of 10) of studies Vera-Rodriguez et al, 2018;Capalbo et al, 2018). Embryonic cf-DNA differs in size and contains different preferred ends than maternal fragments (Chan et al, 2016;Peng and Jiang, 2017). These features could be used to develop new approaches that will allow discriminating embryonic cf-DNA from exogenous DNA in SCM to improve SCM-PGT sensitivity and specificity.…”
Section: Reliability Of Non-invasive Preimplantation Genetic Testing mentioning
confidence: 99%